The Effect Of Using Youtube Videos As Media To Improve Listening Comprehension Of Narrative Text In Vocational School Surabaya - Arini, Tiyasa Nindya; Kuswardani , Rahayu (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research examines the impact of audio visual media, particularly YouTube, on students’ listening comprehension in vocational schools. A quasi experimental design was applied by dividing participants into experimental and control groups, each consisting of thirty five eleventh grade students from a vocational school in Surabaya. The study was carried out over five meetings, with listening tests used to measure students’ progress before and after the treatment. The results showed significant improvement in the experimental group exposed to YouTube based learning activities. Their average score increased from 42.57 in the pre test to 68.57 in the post test, demonstrating the effectiveness of integrating audio visual resources into the classroom. Statistical testing using the Wilcoxon method confirmed the findings, as the p value was lower than 0.05. Consequently, the alternative hypothesis was accepted, and the null hypothesis was rejected, providing strong evidence of the benefits of YouTube in language learning. In addition to statistical confirmation, the study highlights the broader potential of technology in education. Audio visual media not only make learning more interactive and enjoyable but also provide authentic exposure that stimulates motivation and student participation.